COMPARISON OF LIVER TISSUE MORPHOLOGY AND MORPHOMETRIC INDICATORS IN NORMAL AND POLYPRAGMOUS ANTI-INFLAMMATORY DRUGS IN ALBUM RATS UNDER THE EFFECT OF 4 DIFFERENT ANTI-INFLAMMATORY DRUGS (Multidisciplinary Journal of Science and Technology, 2024)
According to the World Health Organization, polypharmacy is one of the problems of the 21st century. Anti-inflammatory drugs are among the most commonly used drugs. Recently, polypharmacy has become a serious public health problem as a result of iatrogenicity. Reducing the pharmacotherapeutic properties of drugs causes an increase in the cost of treating patients. As a result, it shows that the problem of polypharmacy is not only a medical, but also a social problem, and finding a solution to it is an urgent task.Currently, polypharmacy treatment with anti-inflammatory drugs is used in medical care for patients of all ages. Along with other organs in the body, scientific research is being conducted to study the effect of polypharmacy on the liver, various pathological conditions that occur in the liver under the influence of drugs, as well as the morphological changes of the liver. Diseases that appear in the liver under the influence of drugs, their complications are studied, and methods of treatment and prevention are recommended. However, there are very few studies devoted to studying the morphological changes that can occur in the liver under the influence of several anti-inflammatory drugs at the same time.